SANKSI HUKUM TERHADAP PELAKU KEJAHATAN DENGAN HYPNOSIS - Prasetyo, Bhakti (DiH: Jurnal Ilmu Hukum, 2011)
Hypnosis crime is a conventional crime that has existed since ancient times until today, although it has been around since before this country turns to date we have not had a clause governing criminal offenses. In Empirical hypnosis crime has a lot going on in Indonesia and has many court decisions are fixed (Incracht) that hypnosis criminal act is a criminal offense. The principle of legality to say that "there is no act can be imprisoned except by the power of the criminal provisions of the existing law" means that the person can not be punished without any written rules that govern them.In fact a lot of events that happen in the middle of the community where the event has not been set in criminal law today. Hypnosis crime is one of the many legal issues that occur at this time where the crime is no crime that govern article.Judge looks hypnosis is used as a tool for easy mode or intentions that resulted in harm to another person called a crime and imprisonment sanction that be a lesson to the public or to the law enforcement agencies for to ensure legal certainty and sense of fairness in society.Key words :Penegakkan hukum (law enforcement), Keadilan (Justice),Â  Kepastian (assurance)Sanksi ( Sanction )